2005
DOI: 10.1002/anie.200462294
|View full text |Cite
|
Sign up to set email alerts
|

Very Large Ising‐Type Magnetic Anisotropy in a Mononuclear NiII Complex

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…The ZFS parameters D for these complexes range from -8 cm -1 to 8 cm -1 [83]. In some cases, geometrical changes in the coordination environment induced greater magnetic anisotropy [113]. In the complex [Ni(HIM2-py) 2 NO 3 ]NO 3 (106), Ni II adopts a distorted octahedral geometry that is similar to pseudo-C 2v symmetry (Fig.…”
Section: Edited June 25mentioning
confidence: 97%
See 1 more Smart Citation
“…The ZFS parameters D for these complexes range from -8 cm -1 to 8 cm -1 [83]. In some cases, geometrical changes in the coordination environment induced greater magnetic anisotropy [113]. In the complex [Ni(HIM2-py) 2 NO 3 ]NO 3 (106), Ni II adopts a distorted octahedral geometry that is similar to pseudo-C 2v symmetry (Fig.…”
Section: Edited June 25mentioning
confidence: 97%
“…Many hexa-coordinated metal complexes exhibit magnetic anisotropies [4,12,22,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] and a few recent studies have demonstrated possible SMM-type behavior by the mono-nuclear complexes. It should be recalled that the first reported SMM was a polynuclear complex that incorporated hexa-coordinated Mn II/III ions in a slightly distorted O h geometry [123][124][125][126].…”
Section: Six-coordinated Complexesmentioning
confidence: 98%
“…Others and we have already demonstrated the large effect of the distortion in the coordination sphere on the magnitude and the nature (Ising or XY) of the anisotropy in molecular complexes. [41][42][43][44][45] Recently, X-ray Absorption Spectroscopy (XAS) at the L 2,3 edge of Ni performed on CsNi II Cr III (CN) 6 nanoparticles demonstrated the presence of axially distorted Ni II ions (NiN 6-x O x species) that belong mainly to the particles' surface. [ 29 ] X-ray magnetic circular dichroism (XMCD) studies allowed assessing the orbital contribution (<L Z >), responsible for the magnetic anisotropy, which was found larger for the Ni II surface ions (<L Z > = 0.32) than for those located in the volume (<L Z > = 0.23).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The largest family of SMMs contain anisotropic metal centers linked by oxo-and carboxylate ligands, with Mn 12 O 12 (O 2 CMe) 16 (OH 2 ) 4 being the best characterized example. The complex exhibits superparamagnetic-like behavior owing to the large spin ground state and Ising-type anisotropy derived from the anisotropic metal centers present.…”
Section: Introductionmentioning
confidence: 99%